CARCASS TRAITS, PHYSICOCHEMICAL CHARACTERISTICS AND SENSORY PROPERTIES OF LONGISSIMUS LUMBORUM MUSCLE OF LAMBS AS AFFECTED BY PRE-SLAUGHTER LAIRAGE AFTER ROAD TRANSPORT - Rekan Fariq Salaye; Azad Behanan Sabw (Journal of Animal and Plant Sciences, 2023)
In this study, the effect of lairage on carcass traits, physicochemical parameters, and sensory properties of Longissimus lumborum muscle in lambs transported by road was investigated. Thirty (30) one-year-old Awasi Syrian lambs were randomly allotted into three slaughtering groups. The first group of lambs was not moved and served as a control (NT), while the animals in the other two groups were loaded into an open vehicle covered with straw and transported by road for two hours, followed by 0hours of lairage (T2L0) and 12hours for (T2L12). The collected data demonstrated that lambs that ware given a lairage period before slaughter lost significantly more live weight (p<0.05) than those slaughtered immediately upon arrival at the slaughterhouse. The carcass shrinkage of T2L0 lambs was less (p<0.05) than that of T2L12 and control lambs. On postmortem days 1 and 7, the muscles of T2L0 treated lambs had significantly (p<0.05) less drip loss but more shear force than T2L12- and control-treated lambs. At day 7 postmortem, bacterial counts in the meat of T2L0 lambs were higher (p<0.05) than those of NT and T2L12 lambs, most likely due to a numerical increase in ultimate pH at day 7. In conclusion, the lairage after transit had no effect on meat quality indicators compared to the control group. The meat from lambs in both groups (non-transported and transported with lairage) had a longer shelf life after postmortem aging than when slaughtered immediately upon arrival at the abattoir.
Keywords: Lamb; Lairage; Road transport; Shelf-life; Sensory properties